2021
DOI: 10.2196/24466
|View full text |Cite
|
Sign up to set email alerts
|

Arabic Version of the Electronic Health Literacy Scale in Arabic-Speaking Individuals in Sweden: Prospective Psychometric Evaluation Study

Abstract: Background Health information is often communicated through the internet. It is vital for the end user to have a range of digital skills as well as understand the information to promote their health. There is a valid and reliable 8-item instrument, the Electronic Health Literacy Scale (eHEALS), that evaluates these skills. The number of Arabic-speaking people migrating to Sweden and to other parts of the world is increasing due to unstable military and political situations in their countries of ori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 51 publications
8
25
0
1
Order By: Relevance
“…The Arabic version of the EHL scale was used [28]. It includes eight questions with a Cronbach's alpha of 0.939, indicating excellent reliability.…”
Section: Electronic Health Literacy Scale About Covid-19mentioning
confidence: 99%
“…The Arabic version of the EHL scale was used [28]. It includes eight questions with a Cronbach's alpha of 0.939, indicating excellent reliability.…”
Section: Electronic Health Literacy Scale About Covid-19mentioning
confidence: 99%
“…However, the scale is built based on the context of Britain and America, and only an English version available, so it has to be tested to see if it is also valid in other linguistic situations. As a consequence, researchers from around the world have translated eHEALS into nearly twenty languages for testing and evaluation, including Dutch [ 26 ], Japanese [ 27 ], German [ 28 ], Portuguese [ 29 ], Spanish [ 30 ], Turkish [ 31 ], Italian [ 32 ], Korean [ 33 ], Hungarian [ 34 ], Serbian [ 35 ], Polish [ 36 ], Chinese [ 37 ], Greek [ 38 ], Norwegian [ 39 ], Amharic [ 40 ], Swedish [ 41 ], Arabic [ 42 ], and Indonesian [ 43 ]. The findings indicated that the translated versions have high internal consistency and credibility.…”
Section: Analysis Of Research Focus In E-health Literacymentioning
confidence: 99%
“…Another finding of this review was that most studies included adopted the e-Health Literacy Scale (eHEALS), which has been translated into more than ten languages all around the world [ 41 – 51 ]. Since Norman et al were the first to define eHealth literacy, which was the most widely cited, the majority of researchers tended to select the eHEALS or its translation as the evaluation tool for e-health literacy.…”
Section: Discussionmentioning
confidence: 99%